Gen Z Students’ Acceptance of Accurate and Zahir Accounting Software Using the UTAUT Model - Citra Sarasmitha; Pujangga Abdillah; Ria Mennita; Fitria Wulandari (Fakultas Ekonomi Universitas Kadiri, 2026)
The increasing use of accounting software in accounting education requires a better understanding of students’ acceptance of different accounting applications. However, previous studies have mainly focused on single-platform adoption, providing limited comparative evidence between accounting software systems. This study examines the behavioral intention of Generation Z students toward the use of Accurate and Zahir accounting software within the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. The study focuses on three main determinants: Performance Expectancy (PE), Effort Expectancy (EE), and Facilitating Conditions (FC). A quantitative explanatory approach was employed using primary data collected through questionnaires from 119 undergraduate students who had completed computerized accounting practicum sessions using both applications. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that Facilitating Conditions and Performance Expectancy positively influence Behavioral Intention in both applications. However, Effort Expectancy influenced Behavioral Intention only in the Accurate application and showed no significant effect in the Zahir application. These findings suggest that Generation Z students may evaluate accounting software differently based on usability perceptions and learning experiences.